Assessment of morphological characteristics and quality of turfgrass Zoysia matrella accessions from Indonesia - RAHAYU RAHAYU; AKTAVIA HERAWATI; GANJAR HERDIANSYAH; RADEN AJENG ALMA AZZAHRA KUSUMA PUTRI; ADNAN SOFYAN; QAMAL MUTTAQIN (Society for Indonesian Biodiversity, 2024)
Abstract. Rahayu, Herawati A, Herdiansyah G, Putri RAAAK, Sofyan A, Muttaqin Q. 2024. Assessment of morphological characteristics and quality of turfgrass Zoysia matrella accessions from Indonesia. Biodiversitas 25: 4950-4960. Zoysia matrella is a popular turfgrass species suitable for tropical climates, including Indonesia. However, there are challenges related to the selection of accessions that produce the best quality. This research aimed to assess the morphological characteristics and visual and functional quality of turfgrass Z. matrella collected from various origins in Indonesia. The study combined exploratory surveys to collect Z. matrella accessions across Indonesia and was continued by laboratory experiments at Universitas Sebelas Maret, Central Java, using a Completely Randomized Design (CRD). We used 16 accessions of Z. matrella from 8 provinces in Indonesia to be compared with two commercials, imported accessions as controls. Results showed that Z. matrella accession from Sampit, Central Kalimantan showed the highest plant height of 10.22 cm, the longest root length of 15.72 cm, and the percentage of coverage was 94.06%. Conversely, accession from Marina Semarang had the shortest plant height of 8.35 cm with a percentage of cover of 72.75%. Some local accessions of Z. matrella had comparable visual and functional quality, growth, and morphology characteristics to the commercialized accessions, opening possibilities for the development of new, high-quality Z. matrella cultivars native to Indonesia.